PENGARUH DISIPLIN KERJA PEGAWAI TERHADAP PENINGKATAN KUALITAS PELAYANAN PADA KANTOR KECAMATAM SEKOLAQ DARAT KABUPATEN KUTAI BARAT - K., Yulianis (PREDIKSI, 2012)
From the analysis of the data it is known that the correlation coefficient Product moment generated is r = 0.542. Based on the analysis, it is clear that employee discipline variables have a positive relationship with the variables to improve the quality of care provided to the public. It can be seen from the results of an empirical comparison between the values of r (count) with the theoretical value of r (table) in the table of critical prices for product moment r, ie r (hit) = 0.542> r (tab) = 0.325 at a significance level of 0 , 05 for n = 37. This means that there is a positive relationship between the variables of employee discipline with variable service quality improvement.Based on calculations made for hypothesis testing using t-test, can result in t (hit) = 3.817, the results of these calculations show that t is greater than t table contained in the tables prices of critical student-t for n-2 at the 0.05 level, ie t (hit) = 3.817> t (tab) = 1.690. This means that there is a positive and significant effect of the variable labor discipline employees for improving service quality variables. Thus it can be said that the formulation of the problem in the study have been answered and the hypothesis can be verified.